Economic Explanations of Earnings Distribution Trends in the International Literature and Application to New Zealand - Jeff Borland (New Zealand Government, The Treasury, 2000)
This report, commissioned by the Treasury, reviews the international and New Zealand evidence on trends in the distribution of earnings over the past 20 years. It assesses the international evidence on the strength of the various explanations for changes in the earnings distribution. It concludes with suggestions on how the trends in the earnings distribution in New Zealand might be further analysed. Considerable variation has occurred in trends in the distribution of earnings between industrialised economies, with English speaking countries showing the greatest increases in earnings inequalities, and European countries showing the least. The New Zealand evidence also shows a growth in earnings inequality, and indicates that this has been due to both growth in inequality in wage rates and in weekly hours of work. Trends in earnings inequalities together with changes in the distribution of employment appear to explain much of the movement in income inequality in New Zealand. The international literature has attributed changes in the distribution of earnings to labour supply side factors (eg, education, age, gender), demand side factors (eg, technological change, international trade), and institutional factors (eg, union effects, labour market regulation). The relative importance of these effects differs between countries. In the United States, where the most detailed analysis has taken place, about one third of the increase in overall earnings inequality can be explained by widening earnings differentials between education/experience groups; and another one-third by institutional factors, primarily declines in the value of minimum wages, and declines in union density. Possible (untested) explanations of the remaining increase include increasing returns to unobserved cognitive or inter-personal skills, and changing social norms. The evidence suggests that the growth in inequality between groups of workers with different levels of educational attainment and experience can be best explained by changes in the demand for and supply of skills. Changes in the relative demand for skill categories appear to be mainly explained by technological change.
Keywords: 330